Correcting Postural Deviations: An Evidence- Supported Shift in Paradigm - Jim Schilling; Seung-Taek Lim; Eunjae Lee (Asian Society of Kinesiology, 2022)
Somatic syndromes of the spinal region may develop secondary to postural dysfunction. Traditionally, emphasis has been placed on correcting postural asymmetries by attempting to change muscle-tendon unit length. The effectiveness of this approach in providing prolonged muscle-tendon unit length changes and optimal postural outcomes has met with controversy. The time has come for a redirection of goals in conservative care for postural dysfunction of the spinal regions. An emphasis needs to be placed on continuous, self-awareness training of postural correction that will facilitate lasting neuromuscular adaptations. The purpose of this review is to rationalize the need to veer from exercises attempting to adjust the muscle-tendon unit length and recognize the evidence-supported impact of simple self-correction strategies meant to facilitate neuromuscular adjustments and correct postural asymmetries.